ANALISIS KELAYAKAN E-AUDIT UNTUK PEMERIKSAAN KEUANGAN PADA KANTOR BPK PERWAKILAN PROVINSI NTT - Leopoldus Soka Riwu; Dwi Prilaswanti (University of Merdeka Malang, 2019)
This study focuses on the feasibility analysis of the e-audit system usedby the BPK RI inspectors to conduct state financial audits. Feasibility analysis is needed so that the Republic of Indonesia BPK can utilize technology that can add value from the results of the inspection and be able to use technology appropriately in accordance with the process of examining the State's finances. This research is descriptive qualitative research. The main data is obtained from in-depth interviews with BPK examiners and e-audit system development teams. The results of the study show that the e-audit system is feasible to be used in the examination of state finances. However, the researcher suggested that the BPK be more active in capturing the needs of the end user, namely the examiner, so that it can be ascertained by the user needs and schedule of system development in the future and so that the system development is in accordance with what the user needs. In addition, the BPK must also consider starting the selection of Information Technology professional services to assist in the development of eaudit systems because of the high likelihood of the many needs of end users in the future